Approved estimates of the Government of Yobe State of Nigeria 1994 - Government of Yobe State of Nigeria (Yobe, Nigeria: Yobe State Government of Nigeria, 1994)
This volume provides the details of approved estimates of the Government of Yobe State of Nigeria 1994
aia 19/02/2019
Loans
Keywords: Budget; Expenditures, public; Nigeria